Prenatal Predictors of Postnatal Quality of Caregiving Behavior in Mothers and Fathers. - Hechler, Christine; Beijers, Roseriet; Riksen-Walraven, Marianne; de Weerth, Carolina (Parenting: Science & Practice)
Objective. The quality of parental caregiving has been shown to affect children's development from birth onward. Therefore, it is important to detect parents at risk for low-quality caregiving as early as possible - preferably before birth. Design. Observations of expectant mothers' and fathers' behavior when exposed to infant crying were examined as predictors of the quality of caregiving toward their own infant 6 weeks postpartum. Eighty-eight expectant mothers and 57 of their male partners were tested during the third trimester of pregnancy. Parents were filmed individually while caring for a crying Simulator Infant for 15 min; the quality of their caregiving was rated on sensitivity and cooperation. Also, cognitive interference on a working memory task and the ability to regulate physical force when exposed to infant crying were assessed. When their baby was 6 weeks old, parents were filmed and rated for sensitivity and cooperation during a 15-min interaction with their own infant at home. Results. Prenatal quality of caregiving behavior toward a simulator infant predicted postnatal quality of caregiving toward the own infant in both mothers and fathers. Cognitive interference and the ability to regulate physical force did not predict postnatal quality of caregiving behavior. Conclusions. Expectant parents' quality of caregiving behavior toward a crying simulator infant predicted both mothers' and fathers' postnatal quality of caregiving behavior. Future research is needed to determine whether the simulator infant may be a useful screening instrument and training tool for parenting skills in at risk groups of parents-to-be.